Fungal metabolites with antimicrobial potential isolated ande characterized produced by genus Fusarium: a systematic review of literature (Research, Society and Development, 2022)
The recurrent characterization of the same bioactive compounds by filamentous fungi may cause lack of interest in the biotechnological issue as well as by the industry. The problem raised by researchers is mainly in the form of the standard cultivation process. Many of these fungal microorganisms cannot express their genes and, consequently, do not synthesise new compounds. With this, it is necessary to identify which fungal bioactive metabolites have been characterized so that new compounds can be isolated. Therefore, the aim of this work was to make a survey through the steps of systematic literature review of fungal metabolites isolated and characterized by Fusarium genus. Scielo, Scopus, Lilacs, WebofScience and Medline were used to identify articles published between the years and 1991 to 2020. The key words "Fusarium", "metabolite" and "antimicrobial" were used to separate each article that fit the question established in this work: "Which fungal metabolites isolated and characterized of Fusarium genus that present antimicrobial potential?". After an initial search, 7967 scientific articles were found from all databases. Despite this number, only 438 articles presented bioactive metabolites extracted from the genus. Then, the steps of the systematic review were performed. 64 articles were identified to extract the data. In all, 57 metabolites with antifungal and antibacterial potential were found. Among these, the compounds of the classes quinones and non-ribosomal peptides were the most characterized. Finally, the present work brings a register of bioactive compounds synthesized during the last 30 years to optimize the search for new metabolites produced by the genus Fusarium